A Rare Type of Upper Extremity Injury: Penetrating Injuries Caused by Blunt-edged Items - (:unkn) unknown (WORLD SCIENTIFIC PUBL CO PTE LTD, 2017)
Background: Penetrating upper extremity injury is a common encountered cause of significant loss of labor force and it is generally caused by sharp items. This article presents five rare cases of penetrating hand and forearm injury caused by blunt-edged items in conjunction with a detailed discussion of the mechanism and management of the injury. Methods: Five patients with a mean age of 37.6 were treated for upper extremity trauma caused by blunt-edged items such as corrugated iron fence, garden wires, iron stick or iron safety fence between 2009 to 2014. All patients were operated under general anesthesia after performing detailed physical examination and x-ray imaging. Results: The explorative surgery of the affected limbs revealed no nervous or vascular injury. In two patients, partial tear of the muscles bellies of intrinsic hand muscles (opponens pollicis and adductor pollicis); in two patients, partial extensor digitorum communis tendon laceration and in the remaining patient, partial tear of the third annular pulley were the only encountered injuries. The physical examinations performed in the last visit of each patient revealed, complete healing of the affected limb without any functional, vascular or sensorial deficiency in a mean follow-up period of 19.2 months. Conclusions: Despite their initial horrible appearance, injuries caused by blunt-edged items are quite harmless to the affected limb because they follow weak anatomic spaces of the extremity and cause minimal tissue damage leaving all vascular and nervous structures intact.
Keywords: Penetrating hand injury; Penetrating wrist injury; Blunt-edged item; Hand trauma; COMPARTMENT SYNDROME; HAND; MANAGEMENT; RUPTURE; TRAUMA